AB0637 Subclinical atheromatosis and vitamin d deficiency in patients with scleroderma. (15th June 2017) - Martin, JJ Gonzalez; Carrion, O; Abdelkader, A; Calvo, E; Aramburu, F; Sainz, F; García de la Peña, P
Abstract : Objectives: To study whether patients with systemic sclerosis (SSc) have an increased cardiovascular risk (CVR), measured on the basis of analytical, angiodinamic and/or vascular lesions on carotid ultrasound. The carotid IMT is a marker of cardiovascular morbidity and mortality, allowing measurement and monitoring of atherosclerosis in asymptomatic individuals, being surrogate markers of future coronary disease, stroke and general death in the general population and in inflammatory rheumatologic diseases. Methods: Epidemiological and analytical data were collected, including the determination of the RCV SCORE index. Vascular ultrasound protocol included assessment of carotid intima-media thickness (IMT), presence of atheromatous plaques, and exploration of peripheral arteriopathy using the ankle arm index (ABI). Results: Seventy adult patients with ES diagnosis (ACR-EULAT 2013 criteria) were included. 94% of the women had a mean age of 50.2±12.5 years, and an average evolution time of 3.0±4.4 years. The distribution by subgroups was: limited SSc (48%), diffuse SSc (34%), pre-SSc (4'2%), sine SSc (2.8%), MCTD (5'7%) and overlap syndrome 4'2%). The mean SSRm was 9.3±7.0 (range 0–42). The ANA were positive in 91.4%, ACA (51.4%), ATA (10%), RNA polymerase (4'2%). 4% were DM, 7% were obese, 11% were active smokers, 13% were HTN, and 28% were ex-smokers. 28% had hypercholesterolemia with a mean total cholesterol of 192.5 (SD ± 31.9) and LDL of 102.4 (SD ± 29.4 mg/dL). 57% received vasodilators, most of them ARA-II. 10% bosentan, 4.2% sildenafil, and a 2.8% combination therapy. The percentage of immunosuppressive drugs was corticoid (50%), MTX (34%), mycophenolate (3%), AZA (11%), HCQ (14%), CP %). The IMT presented pathological values (>0.9 mm) in 39% of the sample, 23% had atheroma plaques (being bilateral in 40%). Subclinical atheromatosis affected 41.4% (patients without cardiovascular events, pathological IMT and/or atheroma plaques). The ABI had pathological values (<0.9) in 17% of the patients. In the bivariate analysis, the pathological GIM was related to the presence of ACA antibodies (OR =3.80, 95% CI: 1.15–12.52, p=0.028) and with the SCORE index of CVR (OR =2.93, 95% CI: 1.12–7, 64, p=0.028); And the presence of atherosclerotic plaques was associated with increased SSRm score (OR 1.09, 95% CI 1.00–1.19, p=0.046), and the highest CVR SCORE index (OR 3.90, 95% CI: 1.31–11.56, p=0.014. In the multivariate analysis, the serum vitamin D concentration showed a protective effect on IMT (OR =0.94, 95% CI 0.89–0.99, p value =0.025); And the main determinant of atheromatous plaques is the SCORE index, since the increase of one unit in SCORE index multiplies by 4 the probability of presenting plaques (OR =4.06, 95% CI: 1.31–12.60; P=0.015), once the effect of SSRm was controlled. Conclusions: 40% of the patients had pathological IMT values, showing association with the presence of positive AAC and the SCORE risk index. The serum concentration of 25-OH-vitamin D showed a protective effect on IMT. Sixty percent of the sample had vitamin D deficiency. The presence of atheromatous plaques (23% of patients) was associated with higher SSRm indexes and SCORE cardiovascular risk. Disclosure of Interest: None declared